Field Pull-Out Test and Analysis of Fiberglass Anchors in Sanshandao Gold Mine - Qingbiao Wang; Zhongjing Hu; Hongyue You; Haolin Xu; Lujie Bai; Shanghuan Yang; Ming Zhang; Zhenyue Shi (Geofluids)
The Sanshandao gold mine is developed near the sea and has high-chloride ion content in the groundwater, resulting in serious corrosion of metal anchors and difficulty in maintaining metal anchors. To solve the corrosion problem of anchor rods in Sanshandao, the use of fiberglass anchor rods, instead of metal anchor rods, is proposed. To verify the feasibility of fiberglass anchor application, a fiberglass anchor (diameter: 27 mm) pulling test was conducted at the Sanshandao gold mine. The test results show that (1) the pull-out resistance of fiberglass anchor rods is better than those of metal pipe slit anchor rods and threaded anchor rods currently used in the Sanshandao gold mine; (2) the failure of fiberglass anchor rods is mainly because of the destruction of anchor washer discs and nuts, whose rods play only 69.90–77.7% of their performance and remain intact; (3) the fiberglass anchor rod was damaged to different degrees several times before the pulling failure, and the damage was accompanied by sound; (4) the fiberglass anchor continued to bear pressure after each damage until complete failure occurred; and (5) the anchor washer disc relative to the nut to allow the pressure effect can avoid nut pressure collapse and improve the pulling performance of the anchor rod to a certain extent simultaneously. Through the test, it was proved that the 27 mm fiberglass anchor can meet the support demand of the Sanshandao gold mine. It also provides an important reference for the promotion and application of fiberglass anchor rods in similar mines.